The handbook of the neuropsychology of language - Faust, Miriam (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
This handbook provides a comprehensive review of new developments in the study of the relationship between the brain and language, from the perspectives of both basic research and clinical neuroscience. Includes contributions from an international team of leading figures in brain-language research. Features a novel emphasis on state-of-the-art methodologies and their application to the central questions in the brain-language relationship. Incorporates research on all parts of language, from syntax and semantics to spoken and written language. Covers a wide range of issues, including basic level and high level linguistic functions, individual differences, and neurologically intact and different clinical populations.
v. 1. Language processing in the brain : basic science -- v. 2. Language processing in the brain : clinical populations.
Includes bibliographical references and index.
Print version record.
Keywords: Neurolinguistics -- Handbooks, manuals, etc; Language; Neuropsychology -- methods; Brain -- Physiology; Linguistics -- methods; Electronic books